The Influence Of Service Quality Kesehatan Pasien Polyclinic Brand Image To Hospital Tk. III dr. Reksodiwiryo Padang - Shanty Maria Fernanda Lissanora; Azis Mangara (Benih : Journal of Midwifery, 2025)
Increased competition due to customers who increasingly selective and knowledgeable in choosing a hospital, the Hospital requires Tk.III dr. Reksodiwiryo Padang as a provider of health care to always improve the quality of service. In order to improve the quality of care, it must first be known whether the service rendered to the patient during the patient has been in line with expectations or not that will affect the brand image of the hospital. The purpose of this study is to analyze the relationship between service quality and brand image Tk Hospital. III Dr. Reksodiwiryo Padang. The study was conducted in April 2013. The study population consists of 538 patients. So the total sample of 108 patients, obtained by stratified random sampling. Questionnaire data collection by using a questionnaire. Data were analyzed using multiple regression test. The results showed that the partially positive relationships between all the variables that variable service reliability (dependability), responsevensess (responsiveness), assurance (security), empathy (empathy), tangible (real evidence) to Brand Image Hospital Tk.III dr. Reksodiwiryo Padang. And there is a significant relationship between the variable reliability (dependability), responsevensess (responsiveness), assurance (security), empathy (empathy), tangible (real evidence) to Brand Image Hospital Tk.III dr. Reksodiwiryo Padang. However, there is no significant relationship between assurance (security), empathy (empathy) toward Brand Image Tk.IIIdr Hospital. Reksodiwiryo Padang. Simultaneously, a significant difference between the services of the Brand Image Hospital Tk.III dr. Reksodiwiryo Padang (siginifikasi value 0.000). Based on the value of the coefficient was found that the most influential variable on Brand Image in Hospital Tk.III dr. Reksodiwiryo Padang is variable tangibles / physical evidence (X1), where the significance value 0.004 and 0.365 beta value. To the House leadership suggested SakitTk.III dr. Reksodiwiryo Padang to conduct training programs for all care workers on how to give good service to patients so as to improve customer satisfaction and increase Brand Imge Hospital Tk.III dr. Reksodiwiryo Padang. For further research to examine the factors - other factors affecting brand image Tk.III Hospital dr. Reksodiwiryo Padang such as leadership and promotion factors